2020
DOI: 10.1177/1557988320936892
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and Peer Health Leadership Intervention Implementation for Men in Dar es Salaam, Tanzania: A Qualitative Assessment of Perceived Economic and Health Outcomes

Abstract: Men in sub-Saharan Africa continue to experience health disparities that are exacerbated by low employment. This study qualitatively assessed men’s perceptions of the economic and health-care-seeking effects of participation in an integrated microfinance and peer health leadership intervention on violence and HIV risk reduction in Tanzania. Three focus group discussions with 27 men, aged 20 to 44 years, examined the perceived effects on income generation, employability, mental health, and uptake of HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This issue of providing for the family may be exacerbated after starting HIV treatment and missing work to seek HIV services. [34][35][36] Inclusion of income-generating activities can encourage men to make the time sacrifice needed and still allow them to provide for their families, thereby maintaining their status and respect within the community. 37 We found that the crowdsourcing contest generated strong online interest as suggested by Facebook followers, submissions received, and the comparative reach of the finalist images.…”
Section: Discussionmentioning
confidence: 99%
“…This issue of providing for the family may be exacerbated after starting HIV treatment and missing work to seek HIV services. [34][35][36] Inclusion of income-generating activities can encourage men to make the time sacrifice needed and still allow them to provide for their families, thereby maintaining their status and respect within the community. 37 We found that the crowdsourcing contest generated strong online interest as suggested by Facebook followers, submissions received, and the comparative reach of the finalist images.…”
Section: Discussionmentioning
confidence: 99%